The Behaviour of Netiquette in the Virtual Communication Culture of Mataram University Students : (Netnographic Study in Facebook Group) - Fachry, Muhammad; Faresta, Rangga Alif; Zm, Hamidsyukrie; Suud (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
Indonesian netizens were named the most disrespectful netizens in Southeast Asia after the release of the Digital Civility Index (DCI) 2020 by Microsoft. Therefore, it is necessary to read and prepare formulations related to social media among the Indonesian people, especially the younger generation. This study aims to understand netiquette behavior in the virtual communication culture of Mataram University students. This research was conducted using the Netnography method in the Unram New Student Info Facebook group. This research uses a qualitative method. The total membership of the group is 33,700, representing a diverse community in terms of educational background and year of study. Data collection involved depth interviews, observation, documentation, and data triangulation. A sample of 2 informants and 4 subjects was selected for detailed analysis. The data was analyzed in three steps: data reduction, data presentation, and conclusion drawing. The results of this study indicate that, firstly, Mataram University netizens have understood netiquette by extrapolation even though they use other terms. Secondly, the attitude of Mataram University netizens tends to prioritize cognitive aspects in responding to all information on social media. Thirdly, in general, netizens from Mataram University have implemented netiquette well; however, when discussing campus politics or policies perceived as unfavorable to students, their responses tend to be varied and often do not prioritize netiquette.